Intellectual Property Rights protection for rice varieties - status - emerging issues and challenges-new initiatives - Prasanna, PA Lakshmi; Subba Rao, L V; Hari Prasad, A S; Waris, Amtul; Meera, Shaik N; Nirmala, B; Arun Kumar, S; Syamaladevi, Divya P (ORYZA-An International Journal of Rice, 2018)
Study of evolving landscape of Intellectual property right (IPR) protection to rice plant varieties in India, indicates dominance of private sector in hybrid research output. At global level, the issues associated with IPR protection to rice plant varieties are overlapping IPRs, increasing consolidation in seed sector, problems in exercising of farmers' rights. For addressing these issues, some "open source seedâ€ type initiatives and "access to seed index" type incentive mechanisms are being tried out. In India, though Protection of plant varieties and Farmers Rights Act explicitly has some provisions for protecting farmers' rights, its effectiveness in empowering farmers at ground level is yet to be established.